Kanunnama About Devshirma From the Time of Bayezid II (1481-1512) (Prilozi za orijentalnu filologiju, 2024)
As a contribution to the study of devshirma, the paper presents the Kanunnama on the recruitment of janissary youths, which dates from the reign of Sultan Bayezid II (1481-1512). In the introduction, the term devshirma itself is explained and basic information about its origin and implementation is presented. Also, the introductory part includes a short overview of the scientific literature that deals with the process of recruiting young men into the janissaries. The following chapter presents the mentioned kanunnama, basic information about its manuscript copies and historical significance. The most important segment of this work is the integral translation of the Kanunnama on the recruitment of janissary youth, which represents the basis of the functioning of the acemi ocak. The aforementioned kanunnama was compiled into eight legal articles that had to be strictly observed when recruiting young men into the janissaries.